(untitled) (Research, Society and Development, 2023)
Our objective is to review the literature regarding the induction of lactation in transgender women, seeking publications, in any year, that discuss the relevant aspects of this topic. This is an integrative review and its systematization took place through the following steps: a) identification of the guiding question, b) search in the digital literature, c) evaluation of the findings, d) interpretative analysis of the results, e) discussion with summarization of knowledge. For the search, combinations of the following indexing terms were used: lactation, breastfeeding, trans women and transgender women (and their English counterparts). Data collection was carried out during the month of September 2022 in the PubMed, LILACS and SciELO databases. Initially, 27 publications were identified during the search. After applying the inclusion and exclusion criteria, a total of 09 works were obtained for inclusion in this study. It is possible to observe that there is a scarcity of works on the subject in the literature. Breastfeeding is a gender affirmation strategy for trans women and should be encouraged whenever possible. Milk production is possible through a protocol that consists of: stimulation and expression of the breast tissue, use of anti-androgens and galactagogues and increase with subsequent reduction of serum levels of estradiol and progesterone. It is concluded, therefore, that the induction of lactation in transgender women is feasible, economical, accessible and potentially safe. However, it is necessary to encourage research on this topic in order to answer the several remaining questions.